2017
DOI: 10.1155/2017/2825703
|View full text |Cite
|
Sign up to set email alerts
|

Cytoprotective Effects of Citicoline and Homotaurine against Glutamate and High Glucose Neurotoxicity in Primary Cultured Retinal Cells

Abstract: Citicoline and homotaurine are renowned compounds that exhibit potent neuroprotective activities through distinct molecular mechanisms. The present study was undertaken to demonstrate whether cotreatment with citicoline and homotaurine affects cell survival in primary retinal cultures under experimental conditions simulating retinal neurodegeneration. Primary cultures were obtained from the retina of fetal rats and exposed to citicoline plus homotaurine (100 μM). Subsequently, neurotoxicity was induced using e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
4

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 45 publications
1
24
0
4
Order By: Relevance
“…After 48 h, primary retinal cells were characterized for opsin as marker of retinal photoreceptors and plated at density of 2.0 × 10 6 cells for cm 2 . Then, cells were exposed for 96 h to physiological glucose concentration (normal glucose, 5 mM D-glucose); or to high glucose concentration (HG, 30 mM D-glucose) as a model of high glucose-induced acute retinal damage (Davinelli et al, 2017) or to high glucose medium stimulated with a single administration of 50 nM RvD1 (Tian et al, 2009) alone or combined with 20 µM Boc2, the FPR2 antagonist (Hughes et al, 2017). Finally, 24.5 mM D-mannitol was added to normal glucose medium, to obtain a final concentration of 30 mM as high osmotic control group .…”
Section: Isolation Of Retinal Photoreceptorsmentioning
confidence: 99%
“…After 48 h, primary retinal cells were characterized for opsin as marker of retinal photoreceptors and plated at density of 2.0 × 10 6 cells for cm 2 . Then, cells were exposed for 96 h to physiological glucose concentration (normal glucose, 5 mM D-glucose); or to high glucose concentration (HG, 30 mM D-glucose) as a model of high glucose-induced acute retinal damage (Davinelli et al, 2017) or to high glucose medium stimulated with a single administration of 50 nM RvD1 (Tian et al, 2009) alone or combined with 20 µM Boc2, the FPR2 antagonist (Hughes et al, 2017). Finally, 24.5 mM D-mannitol was added to normal glucose medium, to obtain a final concentration of 30 mM as high osmotic control group .…”
Section: Isolation Of Retinal Photoreceptorsmentioning
confidence: 99%
“…Citicoline, a nucleoside derivative, is an indispensable endogenous intermediate in the biosynthesis of phosphatidylcholine, which has been widely demonstrated to play a therapeutic role in the development of central nervous system injury and neurodegenerative diseases, and citicoline has specific effects on promoting brain function recovery and in promoting wakefulness ( Wignall and Brown, 2014 ). Citicoline is a safe and well-tolerated drug without significant systemic side effects, and it has been shown that 100 μM of citicoline is not harmful to retinal cells ( Davinelli et al, 2017 ), and even up to 1000 μM citicoline is not harmful to retinal neuroglial cells in vitro ( Matteucci et al, 2014 ). We found that the protective effect of citicoline is dose dependent, and the viability of HEI-OC-1 cells was highest when the concentration of citicoline was 10 μM.…”
Section: Discussionmentioning
confidence: 99%
“…Additional components of Gangliomix may participate in its neuroprotective efficacy, for instance homotaurine and group B vitamins. Homotaurine is a natural aminosulfonate compound endowed with neuroprotective effects as demonstrated in a rat model of neurodegeneration and in primary retinal cell cultured in neurotoxic conditions [59,60]. In addition, vitamin supplementation may function as potential neuroprotective agents against oxidative stress in glaucoma patients, although the association between serum vitamin levels and glaucoma prevalence in humans remains controversial [22].…”
Section: Discussionmentioning
confidence: 99%